2019
DOI: 10.1155/2019/9607590
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Properties of Baeckea frutescens Branches Extracts in Eliminating Breast Cancer Cells

Abstract: Breast cancer is the leading cause of cancer death in women in over 100 countries worldwide and accounts for almost 1 in 4 cancer cases among women. Baeckea frutescens of the family Myrtaceae has been used in traditional medicine and is known to possess antibacterial, antipyretic, and cytoprotective properties. In this study, we investigated the role of Baeckea frutescens branches extracts against human breast cancer cells. Baeckea frutescens branches extracts were prepared using Soxhlet apparatus with solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…In one study, Baeckea frutescens leaves extracts were found to decrease glucose uptake in two breast cancer cell lines (MCF-7 and MDA-MB-231), associated with a cytotoxic and proapoptotic effect. Importantly, the extracts were devoid of cytotoxic effect in the non-tumoral breast cell line MCF10A and were also devoid of effect on glucose uptake [149]. In another study, an extract of Petiveria alliacea leaves and stems reduced glucose uptake and lactate production in the 4T1 breast cell line.…”
Section: Plant Extractsmentioning
confidence: 92%
“…In one study, Baeckea frutescens leaves extracts were found to decrease glucose uptake in two breast cancer cell lines (MCF-7 and MDA-MB-231), associated with a cytotoxic and proapoptotic effect. Importantly, the extracts were devoid of cytotoxic effect in the non-tumoral breast cell line MCF10A and were also devoid of effect on glucose uptake [149]. In another study, an extract of Petiveria alliacea leaves and stems reduced glucose uptake and lactate production in the 4T1 breast cell line.…”
Section: Plant Extractsmentioning
confidence: 92%
“…Cell death was detected using propidium iodide (PI) (Sigma-Aldrich, USA) and acridine-orange (AO) (Sigma-Aldrich, USA) double staining and examined under fluorescence microscope as previously described by [27]. Briefly, 1 × 10 6 MCF-7 cells/ml were plated in 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to using chemical fungicides, plant extracts have attracted the attention of chemical companies as they may be used as botanical fungicides. Baeckea frutescens L. is an important medicinal plant belonging to the Myrtaceae family [ 1 ] and is found in Peninsular Malaysia and Sumatra and distributed along coastal areas of southeastern China and Australia [ 2 ]. B. frutescens has various bioactive properties, such as antibacterial [ 1 , 3 ], antioxidant [ 2 ], anticancer [ 4 ], anti-inflammatory [ 5 ] and insecticidal activities [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baeckea frutescens L. is an important medicinal plant belonging to the Myrtaceae family [ 1 ] and is found in Peninsular Malaysia and Sumatra and distributed along coastal areas of southeastern China and Australia [ 2 ]. B. frutescens has various bioactive properties, such as antibacterial [ 1 , 3 ], antioxidant [ 2 ], anticancer [ 4 ], anti-inflammatory [ 5 ] and insecticidal activities [ 1 ]. The leaves of B. frutescens are rich in various volatile constituents such as terpenoids, sesquiterpenes and phenylpropanoids, which are secondary metabolites associated with numerous bioactivities [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation